New Classics: The Analysis of Classical Music Album Covers’ Digital Age Characteristics - Seker, Cinla (European Scientific Journal, ESJ, 2017)
The aim of this paper is to analyze the digital age characteristics of the classical music album covers at the turning point of the new millennium based on the six main principles of graphic design, which are unity/harmony, balance, hierarchy, scale/proportion, dominance/emphasis, and similarity/contrast visually. The word classic, which based on classes or classifying can define three different aspects of something: the best as quality, the whole as characteristics, and the absolute as and above everything. Music as a mean of artistic expression formed by sound and silence during a time period, according to its components like pitch, rhythm, dynamics, and sonic qualities like timbre and texture. Although European classical art music last its period between 1750 and 1820, the phrase classical music, which first used in 19th century today represents the period between composers Bach (1685-1750) and Beethoven (1770-1827). Since the recording technologies occurred in late 1980’s, another field of design already born developed as a multi complementary discipline. Album cover design is a special department of graphic design, which is the pre-production process of a printed and formatted two-dimensional surface. Album cover design based on six main graphic design principle, which combined to the content, components and the characteristics of the recorded music.